The morphology, D.C Conductivity and Activation Energy of CdS:Zn Films Fabricated by chemical spray pyrolysis - R.Ghanim, Ihsan; R.Kahlil, Mohammed; T. Shihab, Nawras (Al-Qadisiyah Journal of Pure Science, 2018)
Znic doped CdS thin films with different volume percentage (3, 6 and 9) were fabricated by spray pyrolysis technique at a substrate temperature 400oC. The thickness deposited film were 80 nm. Surface morphology test by AFM indicate that the surface of films is smooth and it showed an decrease in (RMS) values with increasing Zinc ratio. It has been making D.C conductivity measurements for all films. The results showed that the conductivity increased with increasing Vol.% Zn , as well as the results showed that all films have two activation energy and this energy increase with increasing Vol.%Zn.